How to Achieve Efficiencies beyond 22.1% for CdTe-Based Thin-Film Solar Cells - I. M. Dharmadasa; A. E. Alam (Energies, 2022)
This review paper summarises the key issues of CdTe and CdS/CdTe solar cells as observed over the past four decades, and focuses on two growth techniques, electrodeposition (ED) and closed space sublimation (CSS), which have successfully passed through the commercialisation process. Comprehensive experience in electrical contacts to CdTe, surfaces & interfaces, electroplated CdTe and solar cell development work led to the design and experimentally test grading of band gap multilayer solar cells, which has been applied to the CdS/CdTe structure. This paper presents the consistent and reproducible results learned through electroplated CdTe and devices, and suggestions are made for achieving or surpassing the record efficiency of 22.1% using the CSS material growth technique.